Cheap assays of malate, glycerol and ethanol in fermenting must and food samples - Gattas, EAL; Tininis, CRCS; Lauce, C. (Medimond S R L, 2003)
A preparation, enriched with malate dehydrogenase (MDH), alcohol dehydrogenase (ADH), glycerol -3- P dehydrogenase (GPDH) and glycerol kinase (GK), was obtained from dry baker's yeast. This preparation was used to assay glycerol, ethanol and malate measuring the variations in absorbance (NADH formation) at 340 nm. Good degrees of recoveries were obtained when glycerol was added to red wine and fermenting sugar-cane juice and when L-malate was added to commercial apple juice samples. Good results were also obtained when ethanol was assayed in fermented sugar-cane juice and wine samples, using both the partially purified preparation obtained from dry yeast and a purified commercial alcohol dehydrogenase.
Keywords: dry baker's yeast; glycerol; ethanol; malate assay